Air embolism during off-pump coronary artery bypass graft surgery -A case report- - Choo-Hoon Chang; Young Hee Shin; Hyun-Sung Cho (Korean Journal of Anesthesiology, 2012)
There have been several reports of gas embolism occurring during off-pump coronary artery bypass graft (OPCAB) surgery. However, all these cases of air embolism were associated with the repair of venous circulation, using a CO2 blower. In this report, we describe a rare case of air embolism in the coronary arteries associated with the use of a CO2 blower during OPCAB. There was no injury to the veins during OPCAB. The air embolism was treated successfully with cardiopulmonary bypass.